Patterns of Food Security and Dietary Intake Among Children Across the U.S. Child Tax Credit Expansion. (14th June 2022) - Adams, Elizabeth; Bean, Melanie; Dugger, Roddrick; Brickhouse, Tegwyn
Abstract: Objectives: Families with lower economic resources are at higher risk for experiencing food insecurity and suboptimal diet quality. During COVID-19, the novel expansion to the U.S. Child Tax Credit (CTC) provided families from lower income backgrounds with unconditional cash assistance ($250–300 per child, each month) from July to December 2021. This additional income has potential to improve food security and diet quality, if spent towards food resources. This study aimed to examine patterns of food insecurity and children's dietary intake before and during monthly CTC payments. Methods: Parents (N = 621) with a child ages 2–10 years who qualified for the full CTC benefit were enrolled. Three online surveys were completed baseline (T0: June 2021) and at two timepoints during (T1: September 2021; T2: December 2021) the CTC expansion. The validated 18-item USDA Food Security Module, NCI Dietary Screening Questionnaire, and Beverage Intake Questionnaire were administered at each timepoint. Repeated measures analysis of variance models will examine changes in dietary intake before and during the CTC expansion. Results: To date, data from T0 and T1 have been analyzed. Late-breaking data that include T2 results will be presented at Nutrition 2022. At T1, after receiving 3 monthly payments, 45.9% of parents reported spending CTC funds on foods/beverages. This was the most commonly reported use of CTC funds, particularly for families with very low food security (63.0%). From T0 to T1, families with very low food security decreased (T0: 12.7% vs. T1: 5.6%), while food security increased (T0: 57.4% vs. T1: 66.4%). Children's consumption of added sugar, sugar-sweetened beverages, and sweetened fruit juice decreased over time (qs < .05). No changes were observed in other dietary components (qs > .05). Conclusions: Initial patterns indicate promise that CTC monthly payments are associated with reduced household food insecurity and lower sugar-sweetened beverage intake among children. This line of research can inform legislative decisions regarding the maintenance of this policy mandate, by enhancing understanding of the CTC expansion's impact on children's food security and nutritional intake. Funding Sources: Child Health Research Institute at Virginia Commonwealth University and NIH (2T32CA093423) for ELA effort.